2011
DOI: 10.1111/j.1439-0531.2011.01790.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Activation Methods on DNA Synthesis and Development of Parthenogenetic Porcine Embryos

Abstract: This study investigated the timing of DNA synthesis and patterns of pronuclear (PN) formation during the first cell cycle, and its influence on developmental competence, velocity and proliferation index of porcine parthenote blastocysts produced by different activation treatments. Oocytes were activated as follows: electrical stimulation (EST), EST combined with 7.5 μg/ml cytochalasin B (EST + CCB), 10 μg/ml cycloheximide (EST + CHX) and 1.9 mm 6-dimethylaminopurine (EST + 6-DMAP) for 3 h. DNA synthesis and PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…We found that combined activation significantly improved the development potential of parthenogenetic embryos than chemical activation or electrical activation only. It was consistent with the previous studies in cattle (Hosseini et al 2008), goat (Kumar et al 2014), and pig (Ock et al 2011). Comparing with Ion chemical treatment, combined treatment of electrical stimuli induced more Ca 2+ oscillations, and it could mimic intracellular events induced by sperm penetration more efficiently (Sun et al 1992).…”
Section: Discussionsupporting
confidence: 91%
“…We found that combined activation significantly improved the development potential of parthenogenetic embryos than chemical activation or electrical activation only. It was consistent with the previous studies in cattle (Hosseini et al 2008), goat (Kumar et al 2014), and pig (Ock et al 2011). Comparing with Ion chemical treatment, combined treatment of electrical stimuli induced more Ca 2+ oscillations, and it could mimic intracellular events induced by sperm penetration more efficiently (Sun et al 1992).…”
Section: Discussionsupporting
confidence: 91%
“…Bone marrow-derived MSCs (BMSCs) from different sources and passages revealed different characteristics regarding differentiation ability, fibroblast-like morphology, proliferation ability, and expression of transcription factors. Oct4, Sox2, and Nanog, which are known as important early transcription factors for regulation of stem cells pluripotency, are expressed in MSCs (Do and Schöler, 2009;Ock et al, 2011). Deletion of Oct4, Sox2, and Nanog in embryonic stem cells (ESCs) resulted in loss of pluripotency and failure to maintain the epiblast (Welstead et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, after IVM, oocytes and cumulus cells were separated from COCs by pipetting approximately 30 times with 0.1% hyaluronidase in a 1.5 mL centrifuge tube ( Van de Velde et al, 1997 ). The cumulus-depleted oocytes were subjected to parthenogenetic activation using two pulses of direct current at 120 V for 60 µs in 300 mM mannitol containing 0.5 mM HEPES, 0.05 mM CaCl 2 •2H 2 O, 0.1 mM MgSO 4 •7H 2 O, and 0.01% polyvinyl alcohol (PVA) and cultured in 7.5 mg/mL cytochalasin B at 38.5 °C in an atmosphere of 5% CO 2 and 100% RH for 3 h ( Ock et al, 2011 ). Subsequently, approximately 40 oocytes were washed thoroughly with the IVC medium, transferred to 500 mL of IVC medium (bicarbonate-buffered PZM-5 supplemented with 4 mg/mL of bovine serum albumin (BSA)) covered with mineral oil in a 4-well culture plate, and incubated at 38.5 °C in an atmosphere of 5% CO 2 and 100% RH for 7 days.…”
Section: Methodsmentioning
confidence: 99%